Front Cover: Availability of Hydrogen Shapes the Microbial Abundance in Biofilm Anodes based on Geobacter Enrichment (ChemElectroChem 18/2020). Issue 18 (24th August 2020) - Korth, Benjamin; Kuchenbuch, Anne; Harnisch, Falk
Abstract : The Front Cover shows a biofilm anode that is obtained through electrochemically driven enrichment in a one‐chamber reactor that is dominated by Geobacter but also colonized by methanogens that cross feed from cathodic hydrogen. More information can be found in the Article by B. Korth et al .